The neural network associated with lexical-semantic knowledge about social groups. (September 2015) - Piretti, Luca; Carnaghi, Andrea; Campanella, Fabio; Ambron, Elisabetta; Skrap, Miran; Rumiati, Raffaella I.
Abstract: A person can be appraised as an individual or as a member of a social group. In the present study we tested whether the knowledge about social groups is represented independently of the living and non-living things. Patients with frontal and temporal lobe tumors involving either the left or the right hemisphere performed three tasks – picture naming, word-to-picture matching and picture sorting – tapping the lexical semantic knowledge of living things, non-living things and social groups. Both behavioral and voxel-based lesion-symptom mapping (VLSM) analyses suggested that social groups might be represented differently from other categories. VLSM analysis carried out on naming errors revealed that left–lateralized lesions in the inferior frontal gyrus, amygdala, insula and basal ganglia were associated with the lexical-semantic processing of social groups. These findings indicate that the social group representation may rely on areas associated with affective processing.